A Guide to Designing Engaged Learning Courses in Community Planning. (September 2020) - Botchwey, Nisha; Umemoto, Karen
This article provides a guide for developing engaged learning pedagogy in the area of community planning. It is based on a capacity-building approach to community planning that emphasizes the strengthening of individual and collective abilities to plan and shape community futures, ideally toward greater equality, livability, and democratic governance. The article discusses a capacity-building approach to community planning and presents a series of steps in designing and teaching a service learning course, with a succession of issues, questions, and considerations in stepwise order that can aid in the design of a course with community capacity building in mind.